The Effect of E-CRM on the Customer Loyalty of McDonald’s Indonesia - Yuliarti Maghfira Annahli; Ratih Hurriyati; Hilda Monoarfa (Prodi S1 Administrasi Bisnis Universitas Sangga Buana YPKP, 2023)
This research is a quantitative research that examines social phenomena with the aim of knowing the effect of E-CRM on Customer Loyalty. The population of this research is Mc Donald's fast food customers in Indonesia. This study took a sample of 96 respondents using simple random sampling. Data collection in this study was in the form of distributing questionnaires to Mc Donald's fast food customers. The data analysis technique used is calculation analysis and inferential analysis with data processing calculation analysis tools using the IBM SPSS version 24 application. After analyzing the data, the results show that there is a positive and significant effect of E-CRM on Customer Loyalty.